Cover Picture: Applications of digital PCR in COVID‐19 pandemic (View 2/2021). Issue 2 (8th April 2021) - Tan, Chianru; Fan, Dongdong; Wang, Nan; Wang, Fang; Wang, Bo; Zhu, Lingxiang; Guo, Yong
Abstract : In article number 20200082, Yong Guo and co‐workers have shown the detection of SARS‐CoV‐2 RNA by digital PCR.